Self-esteem, dukungan sosial keluarga dan career adaptability: Studi pada taruna-taruni pelayaran tingkat akhir - Ramadhani, Dita Rizky; Sulistiani, Wiwik; Aquarisnawati, Puri (Fakultas Psikologi Universitas Hang Tuah, 2024)
The purpose of this study was to investigate the relationship between self-esteem and family social support with career adaptability in final-year cadets of the Sailing Polytechnic. This study used a quantitative approach. There were 159 cadets—107 males and 52 females. This method used the assumption of probability sampling. The method used for data analysis is the product moment and multiple correlation approach. There are 24 items in the career adaptability scale and 10 items in the self-esteem scale. There are 17 items in the family social support scale. Results showed a relationship between self-esteem and career adaptability. There is a correlation between family social support and career adaptability. For the final-year cadets of the Sailing Polytechnic, there is a relationship between career adaptability and family social support. The results validate the positive hypothesis, demonstrating a correlation between self-esteem and family social support and career adaptability among final-year cadets at the Sailing Polytechnic